Carbon and climate implications of rewetting a raised bog in Ireland. (15th August 2022) - Wilson, David; Mackin, Francis; Tuovinen, Juha‐Pekka; Moser, Gerald; Farrell, Catherine; Renou‐Wilson, Florence
Abstract: Peatland rewetting has been proposed as a vital climate change mitigation tool to reduce greenhouse gas emissions and to generate suitable conditions for the return of carbon (C) sequestration. In this study, we present annual C balances for a 5‐year period at a rewetted peatland in Ireland (rewetted at the start of the study) and compare the results with an adjacent drained area (represents business‐as‐usual). Hydrological modelling of the 230‐hectare site was carried out to determine the likely ecotopes (vegetation communities) that will develop post‐rewetting and was used to inform a radiative forcing modelling exercise to determine the climate impacts of rewetting this peatland under five high‐priority scenarios (SSP1‐1.9, SS1‐2.6, SSP2‐4.5, SSP3‐7.0 and SSP5‐8.5). The drained area (marginal ecotope) was a net C source throughout the study and emitted 157 ± 25.5 g C m −2  year −1 . In contrast, the rewetted area (sub‐central ecotope) was a net C sink of 78.0 ± 37.6 g C m −2  year −1, despite relatively large annual methane emissions post‐rewetting (average 19.3 ± 5.2 g C m −2  year −1 ). Hydrological modelling predicted the development of three key ecotopes at the site, with the sub‐central ecotope predicted to cover 24% of the site, the sub‐marginal predicted to cover 59% and the marginal predicted to cover 16%. Using these areal estimates, our radiative forcing modelling projects that under the SSP1‐1.9 scenario, the site will have a warming effect on the climate until 2085 but will then have a strong cooling impact. In contrast, our modelling exercise shows that the site will never have a cooling impact under the SSP5‐8.5 scenario. Our results confirm the importance of rapid rewetting of drained peatland sites to (a) achieve strong C emissions reductions, (b) establish optimal conditions for C sequestration and (c) set the site on a climate cooling trajectory. Abstract : Peatland rewetting has been proposed as a vital climate change mitigation tool to reduce greenhouse gas emissions and to generate suitable conditions for the return of carbon (C) sequestration. In this study, we present annual C balances for a 5‐year period at a rewetted peatland in Ireland. Our results confirm the importance of rapid rewetting of drained peatland sites to (a) achieve strong C emissions reductions, (b) establish optimal conditions for C sequestration, and (c) set the site on a climate cooling trajectory.